TikTok’s Global Takeover: Algorithms, Audiences, and the Future of Social Media - Hayath, Tasmia; Maruf, Tarekol Islam (IIUM Journal of Case Studies in Management, 2025)
This case study looks at the rise of TikTok to prominence and its continued growth in a crowded social media environment. It follows the development of the platform and its rapid adoption globally. The most potent drivers of the success of TikTok are its recommendation algorithm, short video content, and popularity among different groups of users. The study also touches on the governance, branding, global expansion strategies, and acquisition strategies of the platform. Strategic issues such as data privacy, content management, geopolitical tensions, and intergenerational differences in platform perceptions are addressed. The case concludes by examining the future development of TikTok, flexibility with policy development, and its role in the future digital landscape. Keywords: Algorithm, Competitive strategy, Global expansion, Innovation, Business